Analysis of the relationship between the spatial structure and neighborhood urban Sprawl by Using Space Syntax (Case Study: Shiraz City) - ali movahed; Zahra Sahraeyan; mohamad soleimani (نشریه جغرافیا و برنامه‌ریزی, 2019)
Since the beginning of the present century, the changes in urbanization and its physical transformations have had unfavorable consequences on the structure of the Iranian city, so that the current city, without any attention to its initial construction and organization, has been characterized by disruption, irregular (uneven) development and Socio-economic inequalities. Therefore, the study of changes in the spatial and physical structure of urban environments and their orientation towards harmony and spatial equilibrium is necessary in various aspects of physical, social and economic and preventing spatial instability and inequality.Since it is difficult and impossible to understand the structure and frame of cities based on the analysis of all parts of the city. therefore, analyzing the spatial structure of cities in relation to urban development pattern needs to be able to respond to these spatial spatial complexities and help to understand the structure and spatial structure of modern cities .of theories and methods that study the structure and configuration of urban spac is space layout theory. based on this theory, the city structure and  basics.